Respiratory symptoms and lung function in young adults with severe α(1)–antitrypsin deficiency (PiZZ) - Piitulainen, E (BMJ Group, 2002)
Background: Neonatal screening for alpha(1)–antitrypsin (AAT) deficiency was undertaken in Sweden between 1972 and 1974 when 129 infants with severe AAT deficiency (phenotype PiZ) were identified. The cohort has been followed up prospectively. Methods: 124 PiZ subjects, still alive and still living in Sweden, were invited to a follow up examination at about 22 years of age. The check up included a clinical examination, spirometric tests, and a questionnaire on smoking habits and respiratory symptoms. Results: Ninety eight subjects (97 PiZZ and 1 PiZ–) subjects attended the follow up. The mean age of the subjects was 22.5 years (range 19.8–24.8). The mean (SD) forced expiratory volume in 1 second (FEV(1)) was 98 (14)% predicted, vital capacity (VC) was 103 (14)% predicted, and the mean FEV(1)/VC ratio was 83 (7)%. Eighty six subjects had previously undergone spirometric tests. The median follow up time was 4.3 years (range 0.9–7.3). The mean annual change in FEV(1) (% predicted) was –1.2% (95% CI –2.1 to –0.3), in VC (% predicted) was –1.5% (95% CI –2.0 to –0.9), and in the FEV(1)/VC ratio (%) was –0.3% (95% CI –0.7 to 0.2). Twenty eight individuals (29%) reported recurrent wheezing. Fifteen subjects (15%) had been diagnosed by a physician as having asthma. Eighteen subjects reported that they had smoked at some time; 10 were current smokers. The mean number of pack years among the ever smokers was 3.4 (range 0.6–10.5). Ten of 18 ever-smokers and 18 of 80 non-smokers reported recurrent wheezing (p<0.01), while exertional dyspnoea was reported by six ever smokers and 11 non-smokers (p<0.05). Lung function test results did not differ significantly between ever smokers and non-smokers. Conclusions: Young PiZ adults have essentially normal lung function, but have a high prevalence of asthma symptoms. Smoking in these individuals is associated with an increased frequency of respiratory symptoms.